2010
DOI: 10.1155/2010/414676
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the EGF Receptor for Ovarian Cancer Therapy

Abstract: Ovarian carcinoma is the leading cause of death from gynecologic malignancy in the US. Factors such as the molecular heterogeneity of ovarian tumors and frequent diagnosis at advanced stages hamper effective disease treatment. There is growing emphasis on the identification and development of targeted therapies to disrupt molecular pathways in cancer. The epidermal growth factor (EGF) receptor is one such protein target with potential utility in the management of ovarian cancer. This paper will discuss contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 106 publications
0
58
0
Order By: Relevance
“…This work may have clinical significance given that the ovarian tumor environment contains numerous EGFR activators 2 and approximately 35% of all ovarian cancer tumors are positive for activated EGFR. 3,4 Using an in vitro paradigm of EGF exposure of OVCA 433 cells, we found that acute and long-term EGFR activation increases DNMT activity. It is important to note the observed increase in DNMT activity is an increase in total DNMT activity and does not distinguish the relative contributions of the maintenance methyltransferase (DNMT1) or de novo methyltransferases t-test showed a significant increase in DNMt activity in HS68 cells treated with 10 nM EGf, n = 3.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…This work may have clinical significance given that the ovarian tumor environment contains numerous EGFR activators 2 and approximately 35% of all ovarian cancer tumors are positive for activated EGFR. 3,4 Using an in vitro paradigm of EGF exposure of OVCA 433 cells, we found that acute and long-term EGFR activation increases DNMT activity. It is important to note the observed increase in DNMT activity is an increase in total DNMT activity and does not distinguish the relative contributions of the maintenance methyltransferase (DNMT1) or de novo methyltransferases t-test showed a significant increase in DNMt activity in HS68 cells treated with 10 nM EGf, n = 3.…”
Section: Discussionmentioning
confidence: 96%
“…2 The presence of these activators in patient ascites suggests that the tumor microenvironment is under chronic EGFR activation and may account for the observation that approximately 35% of all ovarian cancer tumors are positive for activated EGFR (tyrosine phosphorylated EGFR). 3,4 Overexpression of EGFR, and its ligands, has been detected in ovarian tumors and correlates with poor prognosis. 3,5,6 EGFR is a member of the receptor tyrosine kinase family that possesses intrinsic tyrosine kinase activity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations